Novel Poly Deep Eutectic Solvents Based Supported Liquid Membranes for CO2 Capture - Ishaq, M. (Frontiers Media S.A., 2020)
The poly deep eutectic solvents (PDESs), a potential substituent to ionic liquids, have emerged as relatively new material and have been successfully applied in catalysis, nanotechnology, and, more importantly, in gas separation. Herein, the PDESs were incorporated for the first time in the CO2 capturing membranes to exploit their inherent advantages in the acid gas capture. The PDESs were synthesized by mixing choline chloride (hydrogen bond acceptor-HBA) and two hydrogen bond donors-HBDs (polyacrylic acid and polyacrylamide) separately in different molar ratios. The physical changes of the resulting homogeneous mixture along with the Fourier Transform Infrared confirmed the successful synthesis of the PDESs. Afterward, these PDESs were impregnated into microporous polyvinylidene fluoride (PVDF) membrane support to fabricate supported liquid membranes (SLMs). The gas performance of the prepared PDES-SLMs was tested under pure and mixed-gas conditions for CO2, CH4, and N2. The PDES-SLMs showed a significantly high CO2/CH4 and CO2/N2 selectivities of the order of 55.5 and 60, respectively. To evaluate their practical implication, the SLMs were investigated systematically under different operating conditions such as choline content, temperature, volume fraction of the CO2 in the feed, and the activation energy required for CO2 capture. The synthesized SLMs showed exceptional results in both permeability and selectivity viewpoint. The remarkable SLMs gas performance can be ascribed to the basicity, molar free volume, and the H-bonding strength of the synthesized PDESs. The green potential, low cost, and the promising gas separation performance make theses PDESs a favorable alternative to the competing PILs in capturing the greenhouse acid gases. Â© Copyright Â© 2020 Ishaq, Gilani, Afzal, Bilad, Nizami, Rehan, Tahir and Khan.